Banwa natural science. (Davao City University of the Philippines Mindanao.)
A peer reviewed inter- and multi-disciplinary journal... it publishes scholarly articles within the research thrusts of the University--biosystems and environment, culture and the arts, and policy and management.
The academic journal of the University of the Philippines Mindanao.
Title from cover.
Description based on : Volume 5, Number 1 (2008).
Latest issue consulted : Volume 5, Number 1 (2008).
Serials Collection.
UPiana collection.
Keywords: Natural science -- Periodicals